Evaluation of Optimization Algorithms for Customers Load Schedule - Diaba, Sayawu Yakubu; Elmusrati, Mohammed; Shafie-khah, Miadreza (International Association of Engineers (IAENG), 2021)
This paper introduces a novel concept for customer load scheduling in the Smart Grid (SG). The concept is based on the forthcoming internet of things (IoT). Approximate optimization algorithms are deduced for optimum customer load scheduling, maximization of electric power suppliers performance, and fairness in scheduling customers load. Using these approximate optimization algorithms as constraints, some loads are given priority. Other loads are scheduled in order to control the maximum demand load and electricity bills. To evaluate the effectiveness of the algorithms, we utilize the Mixed Integer Linear Programming (MILP). Simulations are carried out and the impact on reducing the peak-to-average power ratio (PAPR), the electricity bills, and ensuring fairness in customers load schedules are investigated. Simulation results establish that our algorithms significantly cut down on electricity bills, maximizes utility performance, and deliver fairness in customers load schedules.
Keywords: Demand response (DR); electric vehicle (EV); Internet of Things; load scheduling; mixed integer linear programming; mixed integer linear programming optimization algorithms; ower management system (PMS); Smart grid; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|